2013
DOI: 10.1016/j.combustflame.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Laminar oxy-fuel diffusion flame supported by an oxygen-permeable-ion-transport membrane

Abstract: A numerical model with detailed gas-phase chemistry and transport was used to predict homogeneous fuel conversion processes and to capture the important features (e.g., the location, temperature, thickness and structure of a flame) of laminar oxy-fuel diffusion flames stabilized on the sweep side of an oxygen permeable ion transport membrane (ITM). We assume that the membrane surface is not catalytic to hydrocarbon or syngas oxidation. It has been demonstrated that an ITM can be used for hydrocarbon conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Because oxygen is introduced through permeation, the fuel and oxidizer in the sweep side of an ITM are not pre-mixed, leading to the establishment of a non-premixed or diffusion-controlled reaction zone [10]. In such diffusion-supported reactions, the local thermodynamic state including species concentration and temperature play significant roles in establishing stable reactions and determining the reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…Because oxygen is introduced through permeation, the fuel and oxidizer in the sweep side of an ITM are not pre-mixed, leading to the establishment of a non-premixed or diffusion-controlled reaction zone [10]. In such diffusion-supported reactions, the local thermodynamic state including species concentration and temperature play significant roles in establishing stable reactions and determining the reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…8(a). Under these conditions, it has been shown that the extent of homogeneous-phase reactions is significant leading to substantial fuel conversion in the gas-phase and the enhancement of oxygen permeation [17,27], when only homogeneous-phase reactions were modeled. When catalytic surface reactions are also considered, the change in CH4 conversion and oxygen permeation rate are negligible.…”
Section: Homogeneous-phase and Catalytic Surface Reaction Regimesmentioning
confidence: 99%
“…This is attributed to the exothermic reactions being moved from the gas-phase towards the membrane surface. The membrane conducts this reaction heat to the air side and radiates to the reactor walls [17,27]. Compared to conventional catalytic reactors which are essentially adiabatic, ITM reactors experience extensive thermal energy transfer through the membrane.…”
Section: Coupling Of Gas-phase Chemistry and Surface Reactionsmentioning
confidence: 99%
See 2 more Smart Citations